Faktor Risiko Status Gizi Wasting dalam Penerapan Full Day School pada Anak di Pendidikan Anak usia Dini Pesantren Ummusabri Kendari - Abidin, Abidin; Tasnim, Tasnim; Fatmawati, Fatmawati (Jurnal Gizi Ilmiah, 2018)
Wasting is the most prominent health problem in poor countries and developing countries whose impact is very large. In 2013, nationally the prevalence of underweight in children under five was still 12.1 percent, which means that the problem of underweight in Indonesia is still a serious public health problem. This study aims to determine the effect of implementing full day school on nutritional status in early childhood education at the Ummusabri Islamic Boarding School Kendari. This type of research is quantitative research with a case control approach design. The population in this study were all participants of the 2018 Ummusabri Islamic Boarding School Kindergarten, which amounted to 114. The number for the case sample was 26 people and the control sample was 26 people. The results of the odds ratio test show that diet is a risk factor for wasting nutritional status (OR). = 5.727 95% CI 1.645-19.942 > 1), environmental hygiene is not a risk factor for wasting nutritional status (OR = 0.494 95% CI 0.125-1.949 <1), learning method is not a risk factor for wasting nutritional status (OR = 3.068 95% CI = 0.982-9.591 <1), the role of the family is a risk factor for wasting nutritional status (OR = 3.889 95% CI = 1.178 – 12.841 >1). It is hoped that Paud Pesantren Ummusabri Kendari can use the results of this study as information and consideration in increasing awareness of children with malnutrition problems.